2020
DOI: 10.1186/s12884-020-2807-4
|View full text |Cite
|
Sign up to set email alerts
|

Addressing ethnic disparity in antenatal care: a qualitative evaluation of midwives’ experiences with the MAMAACT intervention

Abstract: Background: In Denmark, 13% of all children are born by non-Western immigrant women. The public antenatal care has not adapted to this increased diversity of women. Compared to women coming from Western countries, non-Western immigrant women have an increased prevalence of severe maternal morbidity and higher risks of maternal death, stillbirth and infant death. Suboptimal care is a contributing factor to these ethnic disparities, and thus the provision of appropriate antenatal care services is pivotal to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…This maternal health theme included three papers which specifically investigated maternal health in relation to minority populations (Strohschein et al ., 2010; Huang et al ., 2019; Johnsen et al ., 2020). One of the papers was a systematic review published in 2019 and two papers were qualitative studies published in 2010 (Strohschein et al ., 2010) and 2020 (Johnsen et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This maternal health theme included three papers which specifically investigated maternal health in relation to minority populations (Strohschein et al ., 2010; Huang et al ., 2019; Johnsen et al ., 2020). One of the papers was a systematic review published in 2019 and two papers were qualitative studies published in 2010 (Strohschein et al ., 2010) and 2020 (Johnsen et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This maternal health theme included three papers which specifically investigated maternal health in relation to minority populations (Strohschein et al ., 2010; Huang et al ., 2019; Johnsen et al ., 2020). One of the papers was a systematic review published in 2019 and two papers were qualitative studies published in 2010 (Strohschein et al ., 2010) and 2020 (Johnsen et al ., 2020). The systematic review was a review of 10 qualitative papers which focussed on the language barriers or differences in socio-economic status, and clinical practices that conflicted with local fears and traditional customs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our material did not include premature births; but post‐term pregnancies were more common among women born in low‐income countries. Higher frequencies of post‐term pregnancies are found in some ethnic groups 27,28 . The reason is not well understood or investigated but it has been suggested that there might be a genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…Higher frequencies of post-term pregnancies are found in some ethnic groups. 27,28 The reason is not well understood or investigated but it has been suggested that there might be a genetic predisposition. Only 13% of the total effect on Apgar score <7 at 5 minutes was mediated by variables addressed in our study, and 9% of the mediated path was through cohabitation.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%